(untitled) (Journal of Economic Research & Business Administration, 2015)
Insurance trade Kazakhstan in last time noticeable progress. Under, how not stange, attention in this trade with side mass media not yet repel all interest and positive tendency, bessend in this trade. Think this, namely important event – making Fund security insurance payment, widening list obligatory kind insurance making. Nation Corporation on insurance exsport – designation more important tendency development insurance trade Kazakhstan Republic.